2012
DOI: 10.5267/j.ccl.2012.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and microwave-assisted multicomponent reaction of alkyne, halide and sodium azide catalyzed by copper apatite as heterogeneous base and catalyst in water

Abstract: The conventional and microwave assisted multicomponent synthesis of disubstituted 1,2,3-triazoles from terminal alkynes and in situ generated organic azide using copper apatite catalyst in water is reported. The catalytic activity is intimately connected to the basicity of the catalyst. The best activities were observed with the copper hydroxyapatite. The catalyst could be used ten times without further treatment and activation under controlled microwave heating. The protocol was also applicable for various al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…e alkali metal replacing europium has a much smaller charge and larger size. Some oxygen atoms of each SiO 4 tetrahedron surround both Eu(1) and Eu (2). is leads to a weaker electrostatic interaction of oxygen with the Eu(1) and a stronger electrostatic interaction with Eu(2), respectively, and as a result distorts the geometry of SiO 4 , which is con�rmed by the results presented in Table 5.…”
Section: Journal Of Chemistrymentioning
confidence: 62%
See 1 more Smart Citation
“…e alkali metal replacing europium has a much smaller charge and larger size. Some oxygen atoms of each SiO 4 tetrahedron surround both Eu(1) and Eu (2). is leads to a weaker electrostatic interaction of oxygen with the Eu(1) and a stronger electrostatic interaction with Eu(2), respectively, and as a result distorts the geometry of SiO 4 , which is con�rmed by the results presented in Table 5.…”
Section: Journal Of Chemistrymentioning
confidence: 62%
“…Compounds with apatite-type structure are widely investigated because they can be used as biomaterials [1], catalysts [2], ionic conductors [3], and luminescent materials [4]. Studies on electrical conductivity of these compounds have been motivated by research in which high ionic conductivity of La 9.33 (SiO 4 ) 6 O 2 has been previously determined [5].…”
Section: Introductionmentioning
confidence: 99%
“…It acts as an electron donating group in a way that controls the regioselectivity of the reaction, but also as a good leaving group, avoiding decomposition of the intermediate triazoline with formation of the corresponding triazole. Kale et al (2012) reported a rapid and green approach to achieve 1,4-disubstituted triazoles via three component reactions of alkynes and in situ generated azides in the presence of copper apatite (25% weight) as a heterogeneous and recyclable catalyst in aqueous media without using any base. The yield was same (99%) in both the methods, but it needs 1.5-6 h under conventional heating while it requires only 5-20 min in presence of microwave radiations.…”
Section: Other Cycloadditionsmentioning
confidence: 99%
“…al. 102 synthesized a disubstituted 1,2,3-triazole by reacting phenyl acetylene, sodium azide, and benzyl bromide with copper apatite and water. Conventional methods were conducted at 100 C for 1.5-6 h, while microwave methods were conducted at 80 C and 120 W for 5-20 min.…”
Section: 23-triazolementioning
confidence: 99%
“…Conventional methods were conducted at 100 C for 1.5-6 h, while microwave methods were conducted at 80 C and 120 W for 5-20 min. 102 Pons-Bressy et. al.…”
Section: 23-triazolementioning
confidence: 99%